Popular music in England, 1840-1914 : a social history - Russell, Dave (McGill-Queen's University Press, 1987)
Russell's discussion reflects the broad categories of popular music activity during this period. His first section describes the musical activity generated by moral crusaders, philanthropists, educationalists, and reformers who sought to use music as a method of instilling habits of mind and body in the English working classes. The second studies the musical forms developed by entrepreneurs, particularly in the music halls. The third section focuses on the music and musical institutions produced by the community, illustrating the popular capacity for making as well as enjoying music. Perhaps most important, in this first thorough social history of popular music Russell shows how ideas and experiences gained through various forms of popular musical activity influenced popular political life.